2021
DOI: 10.1111/tbed.14214
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of toxoplasmosis outbreaks in Brazil

Abstract: In Brazil, notification of toxoplasmosis outbreaks and epidemiological investigation is a mandatory activity of health surveillance. We investigated the risk factors for toxoplasmosis during outbreaks, notifications of outbreaks by the health secretary and reports in the literature. Other factors related to the municipalities were determined through the Institute of Geography and Statistics portal. We found that fruits and vegetables were the most described transmission routes in outbreaks, and oocysts were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Unwashed fruits and vegetables and untreated water may also be important routes of T. gondii transmission to women [12]. Although water and foodborne (unwashed fruits and vegetables) transmission have been reportedly among the most frequent routes of toxoplasmosis outbreaks in Brazil [36,37], food distributed herein came from industrial kitchens commercially contracted outside the penitentiary (under tight inspection and food handling practices), as the in-prison kitchen was closed at the beginning of COVID-19 pandemics. Thus, unless contamination occurred during in-prison storage and handling, food and water consumed by inmates herein may be unlikely sources of infection during the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Unwashed fruits and vegetables and untreated water may also be important routes of T. gondii transmission to women [12]. Although water and foodborne (unwashed fruits and vegetables) transmission have been reportedly among the most frequent routes of toxoplasmosis outbreaks in Brazil [36,37], food distributed herein came from industrial kitchens commercially contracted outside the penitentiary (under tight inspection and food handling practices), as the in-prison kitchen was closed at the beginning of COVID-19 pandemics. Thus, unless contamination occurred during in-prison storage and handling, food and water consumed by inmates herein may be unlikely sources of infection during the survey.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that carbonate ester prodrugs could be a useful strategy to overcome the poor pharmacokinetic properties of ELQs for the treatment of toxoplasmosis [ 33 ]. Toxoplasmosis is a common parasitic infection affecting humans in developed countries, and it is a fatal infection to developing foetus and people with compromised immune systems [ 38 , 39 ]. Its prevalence varies between 20% and 80%, and is influenced by age, cultural practices, and environmental factors [ 40 ].…”
Section: Therapeutic Applications Of Quinolone Containing Compoundsmentioning
confidence: 99%
“…A recent casecontrol study carried out in the Netherlands indicated a significant risk of acute toxoplasmosis through the consumption of raw or undercooked meat or meat products (Friesema et al, 2023). In contrast, in a highly endemic country such as Brazil, a compilation of outbreaks data indicated that the suspected meat-source accounted for 21.4%, whereas the environmental route was suspected in 45.2% of toxoplasmosis cases (Balbino et al, 2022). Furthermore, available data on global human toxoplasmosis outbreaks showed that 47.1% were associated with tissue cyst and 44.1% with oocyst ingestion (Pinto-Ferreira et al, 2019).…”
Section: Introductionmentioning
confidence: 99%